Comparative Analysis of Effective Language use in Istiqlal Mosque Friday Sermon Youtube Video Transcripts - Setiawan, Alvin; Aghniasari, Keisha Lalitha; Fawwaz, Farikh Giyats; Putri, Yessha Hanina Hardy; Subekti, Ifni Izzati; Suresman, Edi (Formosa Journal of Sustainable Research, 2025)
This research examines the use of effective language in Islamic preaching, especially in Friday sermons. The focus of this research is on the text of the Friday sermon published by the Istiqlal Mosque management and the YouTube platform. This study analyzes the linguistic strategies of two preachers who had the opportunity to become Friday preachers at the Istiqlal Mosque. Using qualitative descriptive analysis, this research explores the role of rhetorical devices such as analogies, metaphors, and storytelling. The research results highlight that effective use of language, which is rooted in Qur'anic principles such as al-hikmah (wisdom), al-mauidzah al-hasanah (good advice), and al-mujjadi (polite argumentation), plays a role in important in conveying da'wah messages that are persuasive and easy to understand. These findings aim to develop a comprehensive framework for improving da'wah communication so that it can be accepted by diverse audiences in both traditional and digital contexts